The Hypochromic Variant of Mycosis Fungoides in Medical Daily Life - Teixeira Campos, Camila (2020)
Introduction: Our objective was to briefly review the literature on the hypochromic variant of mycosis fungoides and highlight common differential diagnoses. Methods: This article consists of a literature review, and the search for references was performed in the Virtual Health Library (VHL) in Portuguese, English and Spanish, with a total of 47 references retrieved. Results: The hypochromic variant of mycosis fungoides is a rare form of this chronic cutaneous T-cell lymphoma, whose clinical presentation is diversified, giving a challenging and late diagnosis to the disease. As the clinical aspects are similar to common dermatoses such as leprosy and pityriasis alba, this hypochromic variant of mycosis fungoides is underdiagnosed or its diagnosis is delayed. Conclusion: The importance of conducting a detailed anamnesis and physical examination at medical appointments is highlighted for the correct diagnosis of unusual diseases, such as the one described, and to enable primary care to detect common cases ac- curately, referring the others to the dermatologist.